Composition, domination, and similarity level of stand among farmers' cultivated blocks at Wan Abdul Rachman Grand Forest Park - Indriyanto (Jurnal Penelitian Kehutanan Wallacea, 2022)
The tree species preferred by forest farmers are not always the same, so that in each farmers cultivated block it is possible to form forest stands with a certain composition. The research aimed to analyze the composition of tree species, dominant tree species, and similarity level of species composition among the farmer’s cultivated block. The research was conducted from August until December 2020. Data collection was carried out with a vegetation survey using nested rectangular plots with a sampling intensity of 1%. The data collected includes tree species, tree height, basal area, and individual number of each species. Data were analyzed by calculating density, frequency, important value index (IVI), similarity index (IS), and dissimilarity index (ID). The results showed that the composition of forest garden stands in the farmer’s cultivated block was categorized as heterogeneous (mixed stand) with the number of trees species varying from 12 to 18 species. The total number of tree species were 43, consisting of 17 jungle wood species, 18 jungle MPTS species, and 8 agricultural MPTS species. The forest garden stands were dominated by 4 tree species, namely Gnetum gnemon, Durio zibethinus, Aleurites moluccana, and Myristica fragrans, each of which had an IVI>19.91%. The similarity level of forest garden stands composition was very low with an average IS of 0.27 and an average ID of 0.73. Thus, it can be stated that the forest garden stands among the farmer’s cultivated blocks had different compositions with a difference of 73%. The heterogeneity of forest garden stands needs to be maintained and even developed so that the ecological function of the forest is maintained and the non-timber produced is sufficiently diverse to meet the needs of communities living around the forest.